Pengaruh Biaya Politik, Cash Holding, dan Kualitas Auditor terhadap Income Smoothing - Fitriyana Rahmadani; Anita Wijayanti; Rosa Nikmatul Fajri (Ekonomis: Journal of Economics and Business, 2020)
This paper examines the determinants of income smoothing focusing on consumer goods industry sector of BEI of 2014 to 2018 for 24 firms, including 120 observations. The independent variables used are political costs, auditor quality and cash holding. Political costs are proxied by variables of firm size, income tax, and number of employees. Test data analysis using logistic regression. The findings show that firm size indicated negative effect on income smoothing, income tax and number of employees have no effect on income smoothing. Cash holding indicated positive effect on income smoothing, auditor quality indicated negative affect on income smoothing